Experimental study on antiwear properties for blends of jet fuel with bio-components derived from rapeseed oil - Iakovlieva, Anna; Boichenko, Sergii; Vovk, Oksana; Kazimierz, Lejda; Kuszewski, Hubert; Jakubowski, Miroslaw (Eastern-European Journal of Enterprise Technologies, 2015)
Antiwear properties of jet fuel, two kinds of biocomponents derived from rapeseed oil and their mixtures were investigated experimentally. Antiwear properties were estimated by the value of the scuffing load and the limiting load of scuffing applied to the friction pair working in a fuel medium. Biocomponents, mainly rapeseed oil FAME and rapeseed oil FAME modified via vacuum distillation were used during the study. It is found that lubricity of biocomponents is significantly higher comparing to conventional jet fuel. It is explained by the chemical composition of FAME: highly polarity of molecules stipulate their good adsorption at the surface of friction pair. High viscosity of biocomponents due to chemical structure positively influence on their lubricity. Adding biocomponents into jet fuel results in strengthening of boundary film and thus improves antiwear properties of fuel blends. It is determined that FAME modified via vacuum distillation possesses better lubricating ability comparing to standard FAME derived from rapeseed oil. Correlation between viscosity and lubricity of fuel is shown.